2019
DOI: 10.1093/infdis/jiz445
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Hepatitis B Exposure Among People Who Report Using Methamphetamine: National Health and Nutrition Examination Survey 2009–2016

Abstract: Background With the nation’s focus on the opioid crisis, methamphetamine has made a comeback, potentially increasing risk for hepatitis B. We examined factors associated with hepatitis B virus (HBV) exposure among people who reported ever using methamphetamine in a nationally representative survey. Methods We used the National Health and Nutrition Examination Survey to examine factors associated with HBV exposure among partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
1
10
3
Order By: Relevance
“…A recent study concluded that women using methamphetamine were four times as likely to be infected by HBV as males [12]. While our study did not nd sex statistically signi cantly associated with BBV positive result, the odds ratio did indicate that women are more likely to be exposed to HBV compared to men.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…A recent study concluded that women using methamphetamine were four times as likely to be infected by HBV as males [12]. While our study did not nd sex statistically signi cantly associated with BBV positive result, the odds ratio did indicate that women are more likely to be exposed to HBV compared to men.…”
Section: Discussioncontrasting
confidence: 93%
“…According to previous literature [4,5,12,30,31], demographic characteristics (age, gender, race/ethnicity), socio-economic status (poverty index, health insurance, healthcare access, education), sexual activity (number of sexual partners in the past year, sexual identity), and drug use behaviors (number of drug use, IDU, number of times used methamphetamine in lifetime use, age started using methamphetamine) were known factors associated with infection of BBV. Therefore, these variables were included as potential confounders in the analyses.…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…A study characterizing methamphetamine use and HIV serological status in San Diego found that 54% of the people who used methamphetamine were HIV positive [11]. Another study examined risk factors associated with HBV infections among people who used methamphetamine [12]. A prospective cohort study conducted in Canada determined that injecting methamphetamine predicted HCV infection among young, streetinvolved persons with injection drug use (IDU) [13].…”
Section: Introductionmentioning
confidence: 99%